Music Therapy Affects Elderly Sleep Quality - Retna Febri Arifiati; Endang Sri Wahyuni (Poltekkes Kemenkes Surakarta, 2022)
Background: Music therapy will stimulate the release of the hormones melatonin, endorphins, and encephalin, which are able to make the body relax, calm, reduce pain, and cause feelings of pleasure. The purpose of this study was to determine the effect of giving uyon-uyon Javanese-style music therapy to improve the sleep quality of the elderly in Makamhaji Village, Kartasura, Sukoharjo. Methods: A pre-experimental research design with one group pre- and post-design. The study population of elderly people in PWRI Makamhaji Village, Kartasura, and Sukoharjo consisted of 80 respondents. The sampling technique used was the purposive sampling technique. There were 62 respondents in the sample. Uyon-Uyon Javanese Style Music Therapy is variable, independent, and dependent on sleep quality. Pittsburgh Sleep Quality Index (PSQI) instrument. Apply the statistics paired sample T-test to the hypothesis. Results: Statistical tests showed that there was a mean difference before and after treatment of 5.27, with a large difference in the quality of sleep before and after treatment of -6.762 and a p-value = 0.000. Conclusions: There is an influence of Uyon-Uyon Javanese Style Music Therapy to Improve the Quality of Sleep for the Elderly in Makamhaji Village, Kartasura, Sukoharjo. Future researchers can examine more deeply other factors that might become a bias in this study in order to refine and clarify the information from this research.